Differences in digital stress in early adulthood in terms of personality types extraversion and neuroticism - Siti Intan Cahyani; Rahayu Hardianti Utami (Penerbit Universiti Kebangsaan Malaysia, 2024)
Technological developments have opened up social media platforms to find and connect. The various assertions about social media highlight its significant impact on psychological health and well-being, often contributing to what is known as digital stress. Digital stress can be identified from personality type; an extraversion personality has more significant implications than a neuroticism personality. This study aims to understand whether there are differences in digital stress in early adulthood in terms of extraversion and neuroticism personality types. This type of research is quantitative with a comparative approach. The research subjects were 301 respondents aged 18-25 years, and the results were obtained through a purposive sampling technique. The study utilized a questionnaire that included the Digital Stress Scale, an instrument developed to measure digital stress, and the IPIP-BFM-25 scale, which assesses personality traits separately. Data analysis used an independent sample t-test. The study's results were p = 0.000 (p <0.05), which means there is a significant difference between digital stress in early adulthood regarding extraversion and neuroticism personality types. Individuals must make decisions regarding digital media and the internet with valuable goals. For example, to fulfil the need for positive social interactions and relationships for extraversion tendencies and media for self-presentation or expressing comfortable opinions for neuroticism tendencies.